2014
DOI: 10.1002/aqc.2475
|View full text |Cite
|
Sign up to set email alerts
|

Bycatch mortality can cause extirpation in four freshwater turtle species

Abstract: Bycatch of non‐target species in commercial fishing nets can have adverse impacts on their populations. Freshwater turtle populations are particularly susceptible to increases in adult mortality, and freshwater turtles are among the most threatened vertebrates. As a case study, the population‐level impacts of bycatch mortality on freshwater turtles were evaluated in Lake Opinicon, Ontario, Canada, a lake that supports a small‐scale commercial fishery. Using population viability analyses, the impacts of bycatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…, Midwood et al. ), hunting and collecting (Garber and Burger , Nickerson and Pitt , Colteaux and Johnson ), boat strikes (Bulté et al. , Bennett and Litzgus ), and introduced or subsidized predators (Fordham et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Midwood et al. ), hunting and collecting (Garber and Burger , Nickerson and Pitt , Colteaux and Johnson ), boat strikes (Bulté et al. , Bennett and Litzgus ), and introduced or subsidized predators (Fordham et al.…”
Section: Introductionmentioning
confidence: 99%
“…Populations of organisms with slow life-history strategies are vulnerable to even small decreases in adult survivorship, with as little as a 2-3% reduction in survivorship resulting in severe population decline (Congdon et al 1993, 1994, Cunnington and Brooks 1996, Enneson and Litzgus 2008. As with other long-lived organisms, much concern in chelonian conservation has been focused on anthropogenic increases in chronic mortality caused by threats such as road mortality (Steen et al 2006), fishing gear entanglement (Steen et al 2014, Midwood et al 2015, hunting and collecting (Garber and Burger 1995, Nickerson and Pitt 2012, Colteaux and Johnson 2017, boat strikes (Bult e et al 2010, Bennett andLitzgus 2014), and introduced or subsidized predators (Fordham et al 2007). In addition to chronic threats, acute catastrophes have been observed in populations of multiple chelonian species in different ecological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Reed et al (2002) noted the annual removal of two adult female alligator snapping turtles (Macrochelys temminckii) from a total population of 200 would result in a 50% reduction in the population within 50 years. Midwood et al (2015), using population viability analysis to look at long-term effects of commercial bycatch mortality, indicated that an increase in annual mortality exceeding two adult female painted turtles was sufficient to extirpate the population from Lake Opinicon, Ontario, Canada, within 350 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not well known how the bycatch mortality impacts turtle populations. Midwood et al (2015) indicated that population extirpation, resultant of commercial bycatch, could occur among the four turtle species they examined, including painted turtles. Further research modeling bycatch mortality is needed to better understand potential effects on turtle populations.…”
Section: Discussionmentioning
confidence: 99%
“…Detrimental sub‐lethal effects and post‐release mortality remain largely undocumented, yet they can have considerable negative population‐level consequences (Chopin & Arimoto, ; Davis, ; Lewison et al ., ). Unknown additional mortality rates are especially concerning for species that have slow maturation and long generation times (Crowder & Murawski, ; Hall et al ., ; Midwood et al ., ). Injuries and negative physiological effects sustained as a result of bycatch, such as net entanglement (e.g.…”
Section: Introductionmentioning
confidence: 97%